2012
DOI: 10.1007/s00128-012-0901-7
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Cd and Zn Concentrations in Liver and Kidney of European Hare from Different Serbian Regions: Age and Tissue Differences

Abstract: A total of 84 European hares collected from eleven Serbian regions investigated upon cadmium (Cd) and zinc (Zn) presence. Strong statistically significant correlations between Cd concentrations in kidney and liver were registered in animals older than 12 months. Significant differences between Zn concentrations in liver in comparison to kidney were found within every single age group with exception of the oldest. Negative correlation (Ps-Pearson's correlation) between Zn and Cd concentrations were found in liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…The levels of Hg reported in SS1 (0.189 mg/ L) and SS2 (0.369 mg/L) are much higher than the recommended limits by Drinking Water. [14], the level of accumulation in different organs of the fish is attributed to differences in physiological role of each organ, and factors such as regulatory ability, behaviour and feeding habits. The five metals (Pb, Cd, As, Cr and Hg) are some of the most toxic heavy metals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of Hg reported in SS1 (0.189 mg/ L) and SS2 (0.369 mg/L) are much higher than the recommended limits by Drinking Water. [14], the level of accumulation in different organs of the fish is attributed to differences in physiological role of each organ, and factors such as regulatory ability, behaviour and feeding habits. The five metals (Pb, Cd, As, Cr and Hg) are some of the most toxic heavy metals.…”
Section: Resultsmentioning
confidence: 99%
“…They are found even in the biological systems of most people. Factors that determine their toxicity include chemical species, dose, and route of exposure; also, the nutritional status, genetics, age, and gender of exposed individuals [14]. Heavy metals with most carcinogenic effects are Cr, Ni, Pb, Cd, and As.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the extent of accumulation of heavy metals in fish is dependent on the metal types, fish species, and the tissues respectively (Korkmaz Görür et al 2012;Petrović et al 2013). Water chemistry (Driscoll et al 1994) directly affects the accumulation of heavy metal in fish.…”
mentioning
confidence: 99%
“…Metal contamination has become a worldwide problem (Dadar et al 2014;Jankovská et al 2010;Magdaleno et al 2014;Petrović et al 2013). Cadmium (Cd) is an environmental pollutant ranked eighth among the top 20 hazardous substances priority list (Klaassen et al 2009), and human activity has markedly increased the distribution of Cd in the global environment.…”
mentioning
confidence: 99%